Slantlet transform-based segmentation and a-shape theory-based 3D visualization and volume calculation methods for MRI brain tumour - Mohammed Sabbih Hamoud Al-Tamimi, 1975-, author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2015)
Thesis (Doktor Falsafah, Bidang Penyelidikan: Sains Komputer)) - Universiti Teknologi Malaysia, 2015